2022
DOI: 10.1177/00307270221115454
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and weaknesses of organized crop seed production by smallholder farmers: A five-country case study

Abstract: In many countries, smallholder farmers play a key role in food crop seed production. So far, the community roles, operational structures, seed production efficiency, aspects of sustainability, and the social and policy environments in which these groups operate have been poorly studied and described. The present study attempts to better understand these factors by drawing cases from twenty-five seed producer groups in five countries (Vietnam, Uganda, Zambia, Niger, and Guatemala) that deal with nine crops in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These effects are still present five years after formal support for the program ended. Our results are consistent with the few existing studies that find indirect benefits of SPGs on local non‐member households in Nepal and other countries (Dey et al., 2022; Gautam et al., 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These effects are still present five years after formal support for the program ended. Our results are consistent with the few existing studies that find indirect benefits of SPGs on local non‐member households in Nepal and other countries (Dey et al., 2022; Gautam et al., 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Dey et al. (2022) provide qualitative evidence that SPG groups across five countries (Vietnam, Uganda, Zambia, Niger, and Guatemala) and nine crops supply much of the seed offered in their respective local markets. Only one study to the authors’ knowledge quantitatively evaluates spillover benefits of seed production: Gautam et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the theme of climate change and seed production mainly explored how climate-induced stress changes the farmers’ perception and influences the seed channel transition, as well as the impact of climate factors on seed production and quality [ 22 , 49 , 50 ]. In the theme of seed quality and farmers’ efficiency, studies center around the impact of seed enterprises and seed sources on agricultural outcomes [ 51 , 52 ].…”
Section: Visualization Of Existing Content Areas and Research Gapmentioning
confidence: 99%
“…In contrast to such non-profit organizations, decentralized seed producer cooperatives or local seed businesses have a market orientation. Typically owned by farmers, these are small to medium-scale seed enterprises that collaborate with formal sector institutions, including research, extension services, and NGOs to produce seed of local and improved varieties for marketing at affordable prices ( 78 81 ). Several assessments have observed that the embeddedness of such decentralized seed production initiatives in local community organizations contributes to their effectiveness and performance ( 82 ), although questions are raised about the long-term sustainability of the local institutions once external support is withdrawn ( 83 , 84 ), but recent assessments show profitability and sustainability of local market-oriented seed production initiatives ( 85 , 86 ).…”
Section: Seed Productionmentioning
confidence: 99%